Nanocatalytic Efficacy of Silver Nanoparticles Fabricated using Chaetomorpha antennina Algal Extract, Their Characterization, and Its Applications - Kingslin, A.; Kalimuthu, K.; Viswanathan, P. (Journal of Scientific Research, 2022)
Silver nanoparticles (SNPs) were synthesized by using an aqueous extract of the green seaweed Chaetomorpha antennina. Synthesized SNPs were characterized by UV-Visible spectroscopy, FTIR, XRD, FESEM, EDAX, and DLS with Zeta potential techniques. The formation of SNPs is confirmed by the appearance signatory brown color of the solution and a characteristic peak at 452 nm in the UV-Vis spectrum. FTIR spectrum indicated 11 intense peaks with different functional groups in capping the nanoparticles. The SNP lattice is unaffected by other molecules in the algal extract, as revealed in the XRD pattern, and the average size was 21 nm according to the full width at half minimum. FESEM images revealed that the synthesized SNPs are spherical in morphology, with sizes ranging from 69.99 to 99.19 nm. The EDX result indicates that Ag-NPs display an absorption peak at 3 keV shows the presence of the silver element. The obtained zeta potential value of SNPs through the DLS method was –27.4 mV. The seedling growth was positively affected by a specific concentration of SNPs. In the antioxidant activity, the IC50 value was 384.13 μg/mL. The SNPs react with earthworm Lampito mauritii in the mortality rate of 25% and 100% for 3 min.